1989
DOI: 10.1901/jeab.1989.52-167
|View full text |Cite
|
Sign up to set email alerts
|

Variable‐ratio Conditioning History Produces High‐ and Low‐rate Fixed‐interval Performance in Rats

Abstract: Four rats were exposed to an A-B-A-B series of 30 sessions each of variable-ratio 20 (A) and fixed-interval 30-s (B) schedules. Four other rats received 120 sessions of fixed-interval 30 s. The rats with a history of variable-ratio responding subsequently showed primarily high or low response-rate patterns on the fixed-interval schedule without evidence of classical scalloping (i.e., increased rates of responding throughout the interreinforcement interval), except infrequently in 1 rat. The rats exposed to onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
96
2
10

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(117 citation statements)
references
References 29 publications
9
96
2
10
Order By: Relevance
“…Subjects with histories of fixed-ratio (FR) schedules responded at high rates under the Fi schedules, whereas those with differential-reinforcement-of-low-rate (DRL) schedule histories responded at low rates under the same Fi schedules. Similarly, many investigators have shown with nonhuman animals under different schedules that current behaviors were affected by schedules immediately before the current ones (e.g., Nader & Thompson, 1987;Urbain, Poling, Millam, & Thompson, 1978;Wanchisen, Tatham, & Mooney, 1989).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Subjects with histories of fixed-ratio (FR) schedules responded at high rates under the Fi schedules, whereas those with differential-reinforcement-of-low-rate (DRL) schedule histories responded at low rates under the same Fi schedules. Similarly, many investigators have shown with nonhuman animals under different schedules that current behaviors were affected by schedules immediately before the current ones (e.g., Nader & Thompson, 1987;Urbain, Poling, Millam, & Thompson, 1978;Wanchisen, Tatham, & Mooney, 1989).…”
mentioning
confidence: 85%
“…Finally, in Experiment 1, the effects of the remote histories were examined by comparing the responding under an identical Fi schedule between the subjects with different histories. The Fi schedule has been used exclusively to test remote history effects (Cole, 2001;LeFrancois & Metzger, 1993;Weiner, 1969), and is one of the schedules most frequently used for testing immediate history effects (e.g., Baron & Leinenweber, 1995;Urbain et al, 1978;Wanchisen et al, 1989;Weiner, 1964).…”
mentioning
confidence: 99%
“…The relatively recent experimental analysis of how past reinforcement interacts with current contingencies has been undertaken in studies of behavioral histor y effects (e.g., Baron & Leinenweber, 1995;Freeman & Lattal, 1992;Tatham & Wanchisen, 1998;Wanchisen, Tatham, & Mooney, 1989;Weiner, 1965Weiner, , 1969. The general method for the study of behavioral history consists of two conditions.…”
mentioning
confidence: 99%
“…Segundo observações de Cole (2001), os estudos que relataram dados indicadores de que os efeitos da história poderiam ser irreversíveis (e.g., LeFrancois & Metzger, 1993;Urbain et al, 1978 -se considerados os resultados até a fase de introdução da droga -e Wanchisen, Tatham, & Mooney, 1989) realizaram de 15 a 40 sessões na fase de teste (i.e., durante a exposição ao FI) 6 e estudos que relataram efeitos transitórios de curta ou longa duração (e.g., Freeman & Lattal, 1992) realizaram de 60 a 90 sessões. Cole (2001) apontou para o fato de que após 80 a 100 sessões de exposição ao FI seus resultados estavam mais de acordo com os estudos que relataram efeitos transitórios.…”
Section: Os Efeitos Da História Podem Ser Permanentes?unclassified
“…Catania, 1998;Sidman, 1960). Adicionalmente, resultados sugerem que em uma seqüência de exposição FR-FI-FR-FI, o comportamento exibido na segunda exposição ao FI difere, em alguns aspectos, do comportamento exibido na primeira exposição ao FI (e.g., Baron & Leinenweber, 1995;Wanchisen et al, 1989).…”
Section: Considerações Finaisunclassified